The German etanercept registry for treatment of juvenile idiopathic arthritis. Issue 12 (28th April 2004) - Horneff, G; Schmeling, H; Biedermann, T; Foeldvari, I; Ganser, G; Girschick, H J; Hospach, T; Huppertz, H I; Keitzer, R; Küster, R M; Michels, H; Moebius, D; et al.
Abstract : Objective: To describe a registry set up to monitor children treated with etanercept in Germany and Austria. Methods: Giannini's criteria, duration of morning stiffness, number of swollen, tender and contracted joints, adverse events, and reasons for discontinuation were assessed. Results: 322 patients with juvenile idiopathic arthritis (JIA) and 12 additional patients with non-JIA rheumatic diagnoses were included. Therapeutic efficacy was observed from one month after treatment was started. The number of patients with significant improvement and the degree of improvement increased during the first year. The mean (SD) number of tender and swollen joints decreased from 9 (9) and 8.4 (9) to 3.0 (6.5) and 4.5 (7) after one month, and to 2.2 (5.5) and 3.3 (5.5) after three months; morning stiffness decreased from 45 (65) minutes to 12 (30) and 7 (19) after one and three months (p<0.001 for all). Using Gianinni's criteria of 30%, 50%, and 70% improvement, a therapeutic response in JIA patients was achieved in, respectively, 66%, 54%, and 30% after one month, 78%, 61%, and 38% after three months, and 83%, 72%, and 52% after six months. Therapeutic efficacy was lower in patients with systemic onset arthritis. Overall tolerability was good: in 592 patient treatment-years there were 69 reports of adverse events in 56 patients, including one CNS demyelination. There were no opportunistic infections or lupus-like reactions. Treatment was discontinued in 53 JIA patients, in 25 because of lack of efficacy. Conclusion: Etanercept treatment was safe and led to a significant improvement in most JIA patients resistant to conventional treatment.